A study on assessment of Non-Scholastic Abilities in Primary School Children - .E.Ravi Kiran,Md,Mipha, Dr. K. Vijaya (International Journal of Scientific Research and Management (IJSRM), 2015)
The present study aims to assess the non – scholastic abilities in primary school children of a co-educational school in Andhra Pradesh. Students of class I to IV were selected by simple random sampling method . A questionnaire pertaining to each student and containing parameters of non-scholastic abilities was given to the class teacher for assessment . The anthropometric measurements of each student were also taken. Seconday data relating to students scholastic performance, family details like income and occupation were collected from students records maintained in the school .About 35( 44.8 %) of the students showed highest non-scholastic score of 55-60. Females showed a higher score compared to males which was statistically significant. Nutritional status was not seen to have any association with non – scholastic & scholastic abilities of the students. There was a significant association between occupation of the parents of students and non scholastic abilities of the students. Non scholastic abilities are not learned by rote as done with scholastic abilities. There have to be fostered and the onus rest with the parents and the teachers.